Pengaruh Profitabilitas, Likuiditas, dan Struktur Aset Terhadap Struktur Modal Bank, Dimoderasi Ukuran Perusahaan Yang Terdaftar di BEI Tahun 2019-2023 - Nur Fadilla; Yani Suryani (Dharma Ekonomi, 2025)
This study aims to analyze the effect of profitability, liquidity, and asset structure on the capital structure of banking companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period, with firm size as a moderating variable. The research employs a quantitative approach using secondary data obtained from financial statements. The sample was determined through a purposive sampling technique, resulting in 27 banking companies that met the criteria. Data were analyzed using multiple regression analysis and Moderated Regression Analysis (MRA). The results reveal that profitability has a negative and significant effect on capital structure, indicating that banks with higher profitability tend to reduce their dependence on external financing. In contrast, liquidity and asset structure do not have a significant effect on capital structure, suggesting that these factors are less influential in determining debt policy within the banking sector. Furthermore, the MRA results demonstrate that firm size moderates the relationship between profitability and capital structure, implying that larger firms can better manage internal funds to reduce leverage. However, firm size does not moderate the effects of liquidity and asset structure on capital structure. These findings contribute to understanding capital structure determinants in the Indonesian banking industry.